Pengaruh Motivasi, Disiplin dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Pertamina RU III Sumatera Selatan - Anita Fitriyanti; Trisniarty Adjeng Moelyatie; Tobari Tobari (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to determine the effect of motivation, discipline and organizational culture on employee performance at PT. Pertamina RU III South Sumatra. This type of research is associative. Samples in research at PT. Pertamina RU III South Sumatra 104 employees using proportionate stratified random sampling technique. The data used in this study are primary data with a questionnaire data collection method. The data analysis technique used is multiple linear regression. The results of the study show that (1) there is a significant influence between motivation, discipline and organizational culture jointly on the performance of employees of PT. Pertamina RU III South Sumatra (2) There is no significant effect between motivation on the performance of employees of PT. Pertamina RU III South Sumatra (3) There is a significant influence between discipline on the performance of employees of PT. Pertamina RU III South Sumatra (4) There is a significant influence between organizational culture on the performance of employees of PT. Pertamina RU III South Sumatra